The Competences of Generation Z and The Adequate Methods for Learning Based on Technology in Higher Education - Dana ATANASESCU; Gabriela PROSTEAN; Andra DIACONESCU (Communications of International Proceedings, 2021)
In the present in higher education are identified and implemented new learning methods adapted to the transformations of the society and to the specific needs of the new generation - Generation Z. The leaning methods  that are innovative based on technology are used to ensure the acquirement by the students of the competences and abilities that are necessary for the 21st century. Starting from these premises the present paper achieves a critical analysis of the learning methods. The methods are analyzed on one side by reporting to the specific of the generation Z and on the other side to the type of competence/ability that is going to be acquired. Of all the methods identified the ones that use technology prevail, consequently in the final part of the analysis is shown the connection between the learning methods, their results and the relevance of digital competences on the labor market.
Keywords: Generation Z; innovative methods; online learning; digital skills